Boronic ester bonds crosslinked vitrimer elastomers with mechanical robustness, shape memory, self-healing and recyclability properties. (29th September 2022) - Huang, Lingyun; Yang, Yinxin; Niu, Zhen; Wu, Ruiyao; Fan, Weifeng; Dai, Quanquan; He, Jianyun; Bai, Chenxi
Abstract: Permanently cross-linked networks confer chemical and mechanical stability to cross-linked elastomers, making their recycling a serious environmental issue. Recyclable covalently crosslinked elastomers have recently been developed by building covalently adaptive networks in elastomers. Here, we demonstrate a simple and general strategy to construct covalent adaptable networks with mechanical robustness, self-healing, shape memory, and recyclability. The dynamic boronic ester linkage between silica and epoxidized natural rubber endows the material with high stretchability and high tensile strength. The boronic ester bond exchange enables the cross-linked network to achieve self-healing, remodeling, and shape memory through network structural rearrangement. The materials can be recovered by hot pressing or dissolution, and the structure of the sample recovered by dissolution remains basically unchanged. Furthermore, a self-healing flexible electronic device can be fabricated by spraying conductive graphite on the surface of these elastomers. Considering that this interfacial boronic ester bond cross-linking can be easily achieved between different commercial epoxy polymers and hydroxyl-rich nanoparticles, we believe that this work has great potential in the development of rubber-based vitrimer elastomers and flexible wearable devices. Graphical abstract: Image 1